Serological characterization of genotypically distinct enteric and respiratory bovine coronaviruses - Ukena, Alexa (Kansas State University, 2015)
Bovine Coronavirus (BCoV) is known to cause enteric and respiratory diseases, such as calf diarrhea, winter dysentery, calf respiratory disease, and bovine respiratory disease complex (BRD). All of these diseases are believed to be caused by the same genotype of BCoV. BCoV exhibits tissue tropism for both the gastrointestinal and respiratory tracts. This tropism is due to 9-O-acetylated sialic acid receptor on both epithelial cells in the respiratory and enteric tract. Currently, the only vaccine available for BCoV targets the enteric form of the disease. This study addresses the hypothesis that antibodies from the enteric form of the disease can cross neutralize the respiratory form of the virus. Data from surveillance studies suggest that BCoV is one of the major contributors to BRD, for which there is no currently approved vaccine for the respiratory form of the disease. Our approach to answering this question is to sequence and analyze the complete genome of 11 respiratory and enteric coronavirus isolates using next generation sequencing (NGS). Following the NGS, viruses were selected based on phylogenetic analysis and ability to grow and be maintained in cell culture. These viruses were then be used as serum neutralization indicator viruses in SN assays. 147 bovine serums submitted to KSVDL were used to determine if there are any serological differences between the immune response to respiratory versus enteric viruses based on the antibodies produced by the animal. The overall results show that there are few differences between the enteric and respiratory isolates at the genomic level and the serological response from the animal to these viruses. The differences between enteric and respiratory virus will need to be further addressed and analyzed to conclude if there is a noteworthy difference between the viruses with different tropisms. Other factors, such as host immune response and environment, are believed to be involved in the virus tropism to certain areas of the body.
Keywords: Bovine coronavirus; Antigenic; Genetic; Vaccination; Respiratory disease; Enteric disease; Veterinary Medicine (0778); Virology (0720)